Laboratory and Clinical Characteristics of Patients Diagnosed With Hellp Syndrome Due To Microangiopathic Hemolytic Anemia and/or Thrombocytopenia - Ekinci, Ömer; Ebinç, Senar (My University, 2020)
Objective: We aimed to present the pregnant patientswho were consulted with hematologists formicroangiopathic hemolytic anemia and/orthrombocytopenia and were diagnosed HELLPsyndrome.Materials and Methods: A total of 32 patients, whowere diagnosed with HELLP syndrome, were included inthis study. Patients with other microangiopathichemolytic anemia, including pre-eclampsia, eclampsia,thrombotic thrombocytopenic purpura, hemolytic uremicsyndrome, disseminated intravascular coagulation etc.were excluded.Results: The median age of all patients was 30.45 ±16.22 (18-52) years. According to the Mississippiclassification; 12 patients (37.5%) were in class 1 while 15patients (46.9%) were in class 2, and there was acuterenal failure in 4 patients (33.3%) in class 1 and 3patients (20%) in class 2. There was no acute renal failurepresent in the class 3 including a total of 5 patients(15.6%). There was renal failure in 6 (42.9%) of 14patients (43.7%) with HELLP syndrome, whosehemoglobin value was less than or equal to 8 gr/dl. Inpatients with HELLP syndrome, the renal failure risk ofthose whose hemoglobin value was less than or equal to8 gr/dl was significantly higher than those whosehemoglobin value was greater than 8 gr/dl (OR: 12.75, p= 0.0285).Conclusion: The mechanism of occurrence of HELLPsyndrome is not clear and have many overlapping clinicalaspects with the other thrombotic microangiopathicsyndromes. Renal failure is a complication of HELLPsyndrome. The most associated cases with renal failureare the presence of DIC and severe anemia in HELLPsyndrome. The hemoglobin value of less than 8 gr/dl is asignificant risk factor for renal failure in HELLPsyndrome.
Keywords: Kadın Hastalıkları ve Doğum; Patoloji; Hematoloji